2021
DOI: 10.1371/journal.pone.0258869
|View full text |Cite
|
Sign up to set email alerts
|

Using a Deliberative Poll on breast cancer screening to assess and improve the decision quality of laypeople

Abstract: Balancing the benefits and harms of mammography screening is difficult and involves a value judgement. Screening is both a medical and a social intervention, therefore public opinion could be considered when deciding if mammography screening programmes should be implemented and continued. Opinion polls have revealed high levels of public enthusiasm for cancer screening, however, the public tends to overestimate the benefits and underestimate the harms. In the search for better public decision on mammography sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Generally, lay people are increasingly becoming more informed of medical terms, conditions, and treatments, which improves comprehension of the potential benefits and harms of screening. However, research has found that information about the different types of harms can be difficult for individuals to relate to their own decision about screening (Jensen et al, 2021 ). Lay people oppositely express great enthusiasm for cancer screening (Degeling et al, 2018 ; Scherer et al, 2019 ; Schwartz et al, 2004 ; Waller et al, 2015 ), and when making the decision to participate in screening, people might not evaluate the benefits and the harms equally (Festinger, 1957 ; Hodson, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, lay people are increasingly becoming more informed of medical terms, conditions, and treatments, which improves comprehension of the potential benefits and harms of screening. However, research has found that information about the different types of harms can be difficult for individuals to relate to their own decision about screening (Jensen et al, 2021 ). Lay people oppositely express great enthusiasm for cancer screening (Degeling et al, 2018 ; Scherer et al, 2019 ; Schwartz et al, 2004 ; Waller et al, 2015 ), and when making the decision to participate in screening, people might not evaluate the benefits and the harms equally (Festinger, 1957 ; Hodson, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In an interview study about continuing mammography screening above the recommended age limit, the women reject the risk of harm by self-exempting themselves from the risk of being harmed or downplaying their reaction to or the importance of the harm [26]. In a deliberative poll study, the women do not only disregard information discordant with their previous beliefs but alter their preferences for mammography screening to fit the information available [27].…”
Section: Assumption 2: the Decision-maker Can Understand And Interpre...mentioning
confidence: 99%